Social change as a lifestyle: identifying actions and practices of vegan activism among young adults - Torres, Rodrigo; Joustra, Camila; Figueroa, Juan; Giacoman, Claudia (Frontiers in Political Science, 2025)
While classical models of social-movement research focus on protests and collective events, recent work has shifted toward an individualized approach to collective action within political participation and activism. Drawing on 73 in-depth qualitative interviews with 40 young vegans in Santiago, Chile, we examine how participants themselves define and enact vegan activism in everyday life. Our results reveal that veganism transcends dietary choice, encompassing professional engagement, online content creation, and even cooking and commensality as deliberate activist practices. These lifestyle-based practices coexist with organized collective actions—like marches and NGO initiatives—to forge a hybrid model of political participation blending individual agency and collective coordination. By integrating these findings into existing theories of lifestyle political activism, we offer a more nuanced framework for understanding political participation. First, we reconceptualize vegan activism as simultaneously a lifestyle movement and a social movement. Second, we introduce a typology that classifies activist actions and practices along the axes of individual versus collective action and interpersonal versus public impact. Third, we uncover underexplored domains—culinary-based actions and professional engagement—that extend current theories of everyday political activism. These findings not only advance theory but also offer practical insights for vegan and environmental activists—such as food-based interventions and digital outreach strategies—to enhance the impact and reach of their practices. By foregrounding activists’ own definitions and experiences in a Global South context, this study demonstrates the value of situated analyses for reconceptualizing political participation and broadening core theoretical frameworks.